Подростковая агрессия в контексте современной социокультурной ситуации - Пилипенко, В.; Волянская, Е. (Социология: теория, методы, маркетинг, 2004)
In the article, there are analyzed social determinants of the teenager aggression, value standards of aggressive behavior, role of the mass media in socialization of aggression. Aggression of person is regarded as a product of social and cultural situation, in the context of norms and values of social system. The sociological interpretation of the teenager aggression phenomenon presented by the work in the context of the current social and cultural situation is based on methodological principles of T.Parsons’s and M.Weber’s theories.